A Closer Look at Low-Performing Adult Readers in the Scandinavian Countries. Issue 2 (23rd February 2020) - Gabrielsen, Egil; Sabatini, John
ABSTRACT: This article focuses on low-performing adult readers in the Scandinavian countries, seeking to identify and describe some of the literacy-related problems that they face. Following a presentation of the Reading Components Assessment (RCA) used in PIAAC (Program for International Assessment of Adult Competencies), we provide profiles for those informants who completed the RCA. Then we compare the RCA results of adults having well-functioning literacy skills with the results of adults identified as low-performing readers. The presentation includes both results for items correct and information about the time used to complete the items. The findings indicate that the gap in performance on the Component task sets is wider between adults scoring Below level 1 in literacy and those scoring on Level 1 than the corresponding gap between Level 1 and Level 2 . Implications for policy and practice are discussed.